Terrestrial Very-Long-Baseline Atom Interferometry: summary of the second workshop - Abend, Sven; Aidelsburger, Monika; Arduini, Gianluigi; Barone, Michele; Beaufils, Quentin; Blas, Diego; Bogojević, Aleksandar; Bongs, Kai; Bortoletto, Daniela; Brand, Christian; Calatroni, Sergio; Calmels, Léo; et al. (EPJ quantum technology, 2025)
This summary of the second Terrestrial Very-Long-Baseline Atom Interferometry (TVLBAI) Workshop provides a comprehensive overview of our meeting held in London in April 2024 (Second Terrestrial Very-Long-Baseline Atom Interferometry Workshop, Imperial College, April 2024 ), building on the initial discussions during the inaugural workshop held at CERN in March 2023 (First Terrestrial Very-Long-Baseline Atom Interferometry Workshop, CERN, March 2023 ). Like the summary of the first workshop (Abend et al. in AVS Quantum Sci. 6:024701, 2024 ), this document records a critical milestone for the international atom interferometry community. It documents our concerted efforts to evaluate progress, address emerging challenges, and refine strategic directions for future large-scale atom interferometry projects. Our commitment to collaboration is manifested by the integration of diverse expertise and the coordination of international resources, all aimed at advancing the frontiers of atom interferometry physics and technology, as set out in a Memorandum of Understanding signed by over 50 institutions (Memorandum of Understanding for the Terrestrial Very Long Baseline Atom Interferometer Study).